KERJASAMA ANTARA KATEKIS DAN ORANG TUA DALAM MENUMBUHKEMBANGKAN IMAN ANAK SEKAMI DI STASI ST. YOSEF BATUAH PAROKI ST. PETRUS DAN PAULUS AMPAH - Antonius Allenby; Silvester Adinuhgra; Paulina Maria Ekasari Wahyuningrum (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2021)
This study aims to describe the cooperation between catechist and parents in developing the faith of the child in the Stasi of Santo Joseph Batuah, the Parish of Santo Petrus and Paulus Ampah. The reason the researchers raised the title of this study is due to the lack of cooperation between parents and catechisms in developing the faith of children in Stasi Santo Yosef Batuah. This is descriptive qualitative research. Data obtained by interviews and documentation. The study was conducted on May 20 - June 2, 2021. The study was conducted at the Stasi of Saint Joseph Batuah Parish of St. Peter and Paul Ampah with a total of 13 informants. Data analysis techniques use Miles and Huberman's model of 3 stages, namely reduction, presentation of data, and conclusion withdrawal.